Preparation method of catalyst for dehydration condensation reduction reaction, obtained product and application
By loading copper oxide-zinc oxide-zirconia-zirconia on activated carbon and calcining and vulcanizing treatment, a catalyst for dehydration, condensation and reduction reaction of aldehyde or ketone and amine was prepared, which solved the side reaction problems caused by the high activity of the existing catalysts and achieved high selectivity and high yield reaction effects.
Patent Information
- Application Number
- CN202411726988.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-28
AI Technical Summary
In the dehydration, condensation and reduction reaction of aldehydes or ketones and amines, existing metal-supported catalysts have high catalytic activity and many types of hydrogenation by-products, which can easily lead to too fast reaction speed, which may cause overtemperature, damage to the catalyst and reactor, and increase safety hazards and production costs.
By supporting copper oxide-zinc oxide-zirconia-zirconia on activated carbon, and by calcining and vulcanization treatment, the hydrogenation catalytic performance of the catalyst is regulated, side reactions are reduced, and the yield of the main product is improved.
In the dehydration, condensation and reduction reaction between aldehyde or ketone and amine, the catalyst has good selectivity, reduced side reactions, improved yield of main products, simple operation, low cost and low environmental pollution.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a catalyst for dehydration condensation reduction reaction and the obtained product, and also relates to application of the catalyst in condensation hydrogenation reaction of aldehyde or ketone and amine. Background Art
[0002] The dehydration condensation reduction of aldehydes and ketones with amines has important applications in the preparation of primary amines, secondary amines and tertiary amines. Organic amine compounds are widely used in many fields such as pesticides, medicines, dyes, surfactants, rubber additives, etc., and play an important role in industrial and agricultural production and daily life.
[0003] Catalytic hydrogenation is a very traditional method, which is to reduce the target amine by dehydration condensation of carbonyl compounds and amines in a reducing atmosphere and a reducing catalyst under a hydrogenation catalyst such as nickel, palladium, or platinum.
[0004] As the application of dehydration condensation reduction reaction of aldehydes and ketones with amines becomes more and more extensive, people's research on it is becoming more and more in-depth. Because metal-supported catalysts have high catalytic activity in dehydration condensation reduction reactions, there are many types of hydrogenation by-products. Especially in the synthesis process of mainstream antioxidant 4020, about 17% of the raw material methyl isobutyl ketone (MIBK) is hydrogenated and reduced to methyl isobutyl carbinol (MIBC) using metal copper as a catalyst. Because these catalysts have strong hydrocracking performance and high activity at the beginning of the start-up, they are prone to excessive reaction speed, which may cause overheating, thereby damaging the catalyst and reactor, which invisibly increases safety hazards, increases production costs, and reduces production efficiency. Summary of the invention
[0005] In order to improve the problems existing in the existing catalysts, the present invention provides a method for preparing a catalyst for a dehydration condensation reduction reaction and the obtained catalyst. The present invention loads copper oxide-zinc oxide-zirconium oxide onto activated carbon through a special process, which can appropriately weaken the hydrogenation catalytic performance of the catalyst, regulate the selectivity in the chemical reaction, reduce the side reactions of the dehydration condensation reduction reaction, and improve the yield of the main product.
[0006] The present invention is achieved through the following technical solutions: A method for preparing a catalyst for a dehydration condensation reduction reaction, the method comprising the following steps: (1) Spreading activated carbon in a fixed bed, and then continuously introducing a mixed solution of copper nitrate, zinc nitrate and zirconium nitrate into the fixed bed so that the mixed solution is in full contact with the activated carbon layer; (2) calcining the activated carbon after being fully contacted with the mixed solution to obtain activated carbon loaded with copper oxide-zinc oxide-zirconium oxide; (3) The activated carbon loaded with copper oxide-zinc oxide-zirconium oxide is dispersed in an organic solvent, and then a sulfiding agent is added to carry out a sulfidation reaction. After the reaction, the mixture is filtered, washed, and dried to obtain a catalyst for a dehydration condensation reduction reaction.
[0007] Furthermore, in step (1), the specific surface area of the activated carbon is 1250-1350 m2 / g.
[0008] Furthermore, in step (1), the thickness of the activated carbon layer on the fixed bed is 1.3-1.8 cm.
[0009] Furthermore, in step (1), the mixed solution is obtained by mixing copper nitrate, zinc nitrate, zirconium nitrate and water, and there is no special requirement for the mixing order of the raw materials.
[0010] Furthermore, in step (1), the concentration of copper nitrate in the mixed solution is 1-5 g / 100 ml, for example, 1 g / 100 ml, 2 g / 100 ml, 3 g / 100 ml, 4 g / 100 ml, 5 g / 100 ml. Preferably, the concentration of copper nitrate is 3 g / 100 ml.
[0011] Furthermore, in step (1), in the mixed solution, the concentration of zinc nitrate is 3-7 g / 100 ml, for example, 3 g / 100 ml, 4 g / 100 ml, 5 g / 100 ml, 6 g / 100 ml, 7 g / 100 ml, preferably, the concentration of zinc nitrate is 4 g / 100 ml.
[0012] Furthermore, in step (1), in the mixed solution, the concentration of zirconium nitrate is 1-5 g / 100 ml, for example, 1 g / 100 ml, 2 g / 100 ml, 3 g / 100 ml, 4 g / 100 ml, 5 g / 100 ml, preferably, the concentration of zirconium nitrate is 2 g / 100 ml.
[0013] Furthermore, in step (1), the mixed solution passes through the activated carbon layer at a certain speed, so that the metal salt in the mixed solution is fully in contact with the activated carbon, and the metal salt is loaded on the activated carbon. The flow rate of the mixed solution is 1-10 ml / min, for example, 1 ml / min, 2 ml / min, 3 ml / min, 4 ml / min, 5 ml / min, 6 ml / min, 7 ml / min, 8 ml / min, 9 ml / min, 10 ml / min, preferably 5 ml / min.
[0014] Furthermore, in step (1), the temperature of the mixed solution when in contact with the activated carbon layer is 25-45° C., for example, 25° C., 30° C., 35° C., 40° C., preferably 35° C. The contact time of the mixed solution with the activated carbon layer is 0.5-2 h, for example, 0.5 h, 1 h, 1.5 h, 2 h, preferably 1 h.
[0015] Furthermore, in step (1), the final loading amount of nitrate on activated carbon can be controlled by controlling the concentration, flow rate and contact time of the mixed solution. In a specific embodiment of the present invention, the final loading amount of copper nitrate on activated carbon is 10-12%, the loading amount of zinc nitrate on activated carbon is 7-8%, and the loading amount of zirconium nitrate on activated carbon is 5-7%. The loading amount is the mass of a certain nitrate / (total mass of activated carbon and nitrate)*100%.
[0016] Furthermore, in step (2), calcination can be carried out in a muffle furnace under an air atmosphere.
[0017] Furthermore, in step (2), the calcination temperature is 400-800°C, for example, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, preferably, the calcination temperature is 500°C.
[0018] Furthermore, in step (2), the calcination time is 2-6 h, for example, 2 h, 3 h, 4 h, 5 h, 6 h, and preferably, the calcination time is 4 h.
[0019] Furthermore, in step (3), the copper oxide-zinc oxide-zirconium oxide loaded activated carbon obtained by calcination can be dispersed in an organic solvent by stirring, ultrasound, etc., and the organic solvent is an alcohol, such as methanol, ethanol, isopropanol, etc., preferably methanol.
[0020] Furthermore, in step (3), the mass ratio of the activated carbon loaded with copper oxide-zinc oxide-zirconium oxide to the organic solvent is 1:6-10, for example, 1:6, 1:7, 1:8, 1:9, 1:10.
[0021] Furthermore, in step (3), the vulcanizing agent is at least one of dimethyl sulfide, dodecanethiol, dimethyl sulfoxide, diphenyl sulfide, and diphenyl disulfide, preferably a mixture of diphenyl sulfide and diphenyl disulfide.
[0022] Furthermore, when the vulcanizing agent is a mixture of diphenyl sulfide and diphenyl disulfide, the mass ratio of diphenyl sulfide to diphenyl disulfide is 1:1-1.5, preferably 1:1.2.
[0023] Furthermore, in step (3), the mass ratio of the copper oxide-zinc oxide-zirconium oxide loaded activated carbon to the sulfiding agent is 5:0.1-1, for example, 5:0.1, 5:0.2, 5:0.3, 5:0.4, 5:0.5, 5:0.6, 5:0.7, 5:0.8, 5:0.9, 5:1.0, preferably 5:0.5.
[0024] Furthermore, in step (3), the vulcanizing agent is preferably added dropwise, and the dropping time is controlled to be 2-5 min. The temperature during the dropping is 25-45°C, for example, 25°C, 30°C, 35°C, 40°C, 45°C, preferably 35°C.
[0025] Furthermore, in step (3), after the vulcanizing agent is dripped, the reaction is continued at 25-45°C, for example, 25°C, 30°C, 35°C, 40°C, 45°C, preferably 35°C. The reaction time is 0.5-2h, for example, 0.5h, 1h, 1.5h, 2h, preferably 1h.
[0026] Furthermore, in step (3), after the sulfurization is completed, the product is filtered, washed and dried to obtain the product of the present invention.
[0027] The catalyst for dehydration condensation reduction reaction of the present invention has good selectivity and can be applied to dehydration condensation reduction reaction of various ketones or aldehydes with amines. Therefore, the catalyst and its application in dehydration condensation reduction reaction of aldehydes with amines or dehydration condensation reduction reaction of ketones with amines are also within the protection scope of the present invention.
[0028] The present invention has the following beneficial effects: 1. The method of the present invention is simple to operate, has mild synthesis conditions, low risk, low cost, and little environmental pollution.
[0029] 2. The present invention uses activated carbon as a carrier, loads metal copper ions, zinc ions and zirconium ions, and then calcines at high temperature to obtain a carbon-based catalyst loaded with a composite oxide, and then uses a sulfiding agent to perform sulfidation to passivate the catalyst activity to obtain the final activated carbon-loaded CuO-ZnO-ZrO2-S catalyst. The catalyst raw materials are very convenient to purchase and transport, and its hydrogenation catalytic performance is appropriately weakened. It can be applied to the dehydration condensation reduction reaction of various ketones or aldehydes with amines, improves the selectivity of the reaction, reduces the products of side reactions, and has a good catalytic effect. DETAILED DESCRIPTION
[0030] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, a novel catalyst preparation method and its application method in antioxidant synthesis proposed in accordance with the present invention, its specific implementation method and its effects are described in detail as follows.
[0031] In the following examples and comparative examples, the activated carbon used was purchased from the market and had a specific surface area of 1250-1350 m2 / g.
[0032] Example 1 A method for preparing a catalyst for a dehydration condensation reduction reaction, wherein the specific synthesis steps are as follows: Step 1: Load Weigh 5g of activated carbon and fill it in a fixed bed with a thickness of 1.5cm. Dissolve copper nitrate, zinc nitrate and zirconium nitrate in water and mix them evenly to obtain a mixed solution with a copper nitrate concentration of 2g / 100ml, a zinc nitrate concentration of 4g / 100ml and a zirconium nitrate concentration of 2g / 100ml. Pass the mixed solution through the fixed bed at a rate of 3ml / min at 35°C, so that the activated carbon and the mixed solution are in contact for 1h. After completion, wash and determine the contents of copper nitrate, zinc nitrate and zirconium nitrate in the remaining mixed solution. Calculate the loading amount of activated carbon by subtraction. The loading amount of copper nitrate on activated carbon is about 10%, the loading amount of zinc nitrate is about 8%, and the loading amount of zirconium nitrate is about 7%. Loading amount = metal salt mass / (activated carbon mass + total mass of metal salt)*100%.
[0033] Step 2: Firing The activated carbon loaded with metal ions was placed in a muffle furnace, calcined at 400° C. in an air atmosphere, and cooled after 3 hours to obtain a carbon-based copper oxide-zinc oxide-zirconium oxide catalyst.
[0034] Step 3: Vulcanization At 25°C, 5g of a carbon-based copper oxide-zinc oxide-zirconium oxide catalyst was added to 30g of an organic solvent, ethanol, and the mixture was fully stirred and dispersed evenly. Then, 0.3g of a mixture of diphenyl sulfide and diphenyl disulfide in a mass ratio of 1:1.4 was dripped therein with a pipette for 3min. After the dripping was completed, the mixture was vulcanized at 25°C for 0.5h, and then filtered, the solid was washed, and dried in an oven to obtain the catalyst product of the present invention.
[0035] Example 2 A method for preparing a catalyst for a dehydration condensation reduction reaction, wherein the specific synthesis steps are as follows: Step 1: Load Weigh 5g of activated carbon and fill it in a fixed bed with a thickness of 1.5cm. Dissolve copper nitrate, zinc nitrate and zirconium nitrate in water and mix them evenly to obtain a mixed solution with a copper nitrate concentration of 3g / 100ml, a zinc nitrate concentration of 4g / 100ml and a zirconium nitrate concentration of 2g / 100ml. Pass the mixed solution through the fixed bed at a rate of 5ml / min at 35°C, so that the activated carbon is in contact with the mixed solution for 0.5h. After completion, wash it and determine the contents of copper nitrate, zinc nitrate and zirconium nitrate in the remaining mixed solution. Calculate the loading amount of activated carbon by subtraction. The loading amount of copper nitrate on activated carbon is about 12%, the loading amount of zinc nitrate is about 7%, and the loading amount of zirconium nitrate is about 6%.
[0036] Step 2: Firing The activated carbon loaded with metal ions was placed in a muffle furnace, calcined at 500° C. in an air atmosphere, and cooled after 4 hours to obtain a carbon-based copper oxide-zinc oxide-zirconium oxide catalyst.
[0037] Step 3: Vulcanization At 25°C, 5g of a carbon-based copper oxide-zinc oxide-zirconium oxide catalyst was added to 30g of an organic solvent, methanol, and the mixture was fully stirred and dispersed evenly. Then, 0.5g of a mixture of diphenyl sulfide and diphenyl disulfide in a mass ratio of 1:1.3 was dripped therein with a pipette for 3min. After the dripping was completed, the mixture was vulcanized at 25°C for 1h, and then filtered, the solid was washed, and dried in an oven to obtain the catalyst product of the present invention.
[0038] Example 3 The catalyst for dehydration condensation reduction reaction was prepared according to the method of Example 2, except that in step 3, 0.5 g of diphenyl sulfide and diphenyl disulfide in a mass ratio of 1:1.3 was replaced by 1 g of diphenyl sulfide, and the dropping time was 3 min.
[0039] Example 4 A catalyst for dehydration condensation reduction reaction was prepared according to the method of Example 2, except that in step 3, 0.5 g of diphenyl sulfide and diphenyl disulfide in a mass ratio of 1:1.3 was replaced by 0.5 g of a mixture of dimethyl sulfide and diphenyl disulfide in a mass ratio of 1:1.2, and the addition time was 3 min.
[0040] Example 5 The catalyst for dehydration condensation reduction reaction was prepared according to the method of Example 2, except that: in step 1, 5g of activated carbon was weighed and filled in a fixed bed with a thickness of 1.5cm. Copper nitrate, zinc nitrate and zirconium nitrate were dissolved in water and mixed evenly to obtain a mixed solution with a copper nitrate concentration of 5g / 100ml, a zinc nitrate concentration of 7g / 100ml and a zirconium nitrate concentration of 5g / 100ml. The mixed solution was passed through the fixed bed at a speed of 10ml / min at 45°C, and the activated carbon was continuously in contact with the mixed solution for 0.5h. After completion, washing was performed, and the contents of copper nitrate, zinc nitrate and zirconium nitrate in the remaining mixed solution were determined. The loading amount of activated carbon was calculated by subtraction, and the loading amount of copper nitrate on activated carbon was about 10%, the loading amount of zinc nitrate was about 7%, and the loading amount of zirconium nitrate was about 5%.
[0041] Comparative Example 1 A method for preparing a catalyst for a dehydration condensation reduction reaction, wherein the specific synthesis steps are as follows: Step 1: Load Weigh 5g of activated carbon and fill it in a fixed bed with a thickness of 1.5cm. Dissolve copper nitrate, zinc nitrate and zirconium nitrate in water and mix them evenly to obtain a mixed solution with a copper nitrate concentration of 3g / 100ml, a zinc nitrate concentration of 4g / 100ml and a zirconium nitrate concentration of 2g / 100ml. Pass the mixed solution through the fixed bed at a rate of 5ml / min at 35°C, so that the activated carbon is in contact with the mixed solution for 0.5h. After completion, wash it and determine the contents of copper nitrate, zinc nitrate and zirconium nitrate in the remaining mixed solution. Calculate the loading amount of activated carbon by subtraction. The loading amount of copper nitrate on activated carbon is about 12%, the loading amount of zinc nitrate is about 7%, and the loading amount of zirconium nitrate is about 6%.
[0042] Step 2: Firing The activated carbon loaded with metal ions was placed in a muffle furnace, calcined at 500° C. in an air atmosphere, and cooled after 4 hours to obtain a carbon-based copper oxide-zinc oxide-zirconium oxide catalyst.
[0043] Comparative Example 2 The catalyst for dehydration condensation reduction reaction was prepared according to the method of Example 2, except that: in step 1, copper nitrate, zinc nitrate and zirconium nitrate were dissolved in water and mixed evenly to obtain a mixed solution with a copper nitrate concentration of 3g / 100ml, a zinc nitrate concentration of 4g / 100ml and a zirconium nitrate concentration of 2g / 100ml. 5g of activated carbon was added to 30g of the mixed solution, stirred and contacted at 35°C for 0.5h, washed after completion, and the loading amount was determined by subtraction method. The loading amount of copper nitrate on the activated carbon was about 8%, the loading amount of zinc nitrate was about 6%, and the loading amount of zirconium nitrate was about 5%.
[0044] Comparative Example 3 The catalyst for dehydration condensation reduction reaction was prepared according to the method of Example 2, except that: In step 1, 5 g of activated carbon was weighed and filled in a fixed bed with a thickness of 1.5 cm. Copper nitrate was dissolved in water and mixed evenly to obtain a solution with a copper nitrate concentration of 3 g / 100 ml. The copper nitrate solution was passed through the fixed bed at a rate of 5 ml / min at 35 ° C, and the activated carbon was kept in contact with the mixed solution for 2 hours. After completion, washing was performed, and the content of copper nitrate in the remaining mixed solution was determined. The loading amount of activated carbon was calculated by subtraction, and the loading amount of copper nitrate on activated carbon was about 17%.
[0045] Comparative Example 4 The catalyst for dehydration condensation reduction reaction was prepared according to the method of Example 2, except that: In step 1, 5 g of activated carbon was weighed and filled in a fixed bed with a thickness of 1.5 cm. Copper nitrate and zinc nitrate were dissolved in water and mixed evenly to obtain a solution with a copper nitrate concentration of 3 g / 100 ml and a zinc nitrate concentration of 4 g / 100 ml. The copper nitrate solution was passed through the fixed bed at a rate of 5 ml / min at 35 ° C, and the activated carbon was continuously in contact with the mixed solution for 0.8 h. After completion, washing was performed, and the content of copper nitrate in the remaining mixed solution was determined. The loading amount of activated carbon was calculated by subtraction, and the loading amount of copper nitrate on activated carbon was about 13%, and the loading amount of zinc nitrate was about 11%.
[0046] Application Example 1 In a 100mL autoclave, 18.4g of 4-aminodiphenylamine, 50g of methyl isobutyl ketone, and 3g of the catalyst of Example 2 were added, and then hydrogen was introduced to 3-4MPa, and the reaction temperature was controlled to be 120°C for ketoamine dehydration condensation. After the hydrogen pressure was lower than 2Mpa, hydrogen was introduced to 3-4Mpa until the hydrogen pressure no longer decreased. After the reaction was completed, it was detected that no by-product methyl isobutyl methanol was detected in the reaction mother liquor, and the remaining ketone and water were removed under reduced pressure to obtain the final antioxidant product 26.29g, the liquid phase purity (HPLC) was 99.2% (after deducting ketone), and the product yield was 98.91% based on 4-aminodiphenylamine.
[0047] Application Example 2 In a 100mL autoclave, 18.4g of 4-aminodiphenylamine, 46.4g of acetone, and 3g of the catalyst of Example 2 were added, and then hydrogen was introduced to 3-4MPa, and the reaction temperature was controlled to be 120°C for ketoamine dehydration condensation. After the hydrogen pressure was lower than 2Mpa, hydrogen was introduced to 3-4Mpa until the hydrogen pressure no longer decreased. After the reaction was completed, it was detected that no by-product isopropanol was detected in the reaction mother liquor, and the remaining ketones and water were removed under reduced pressure to obtain the final antioxidant product 22.34g, the liquid phase purity (HPLC) was 99.1% (after deducting ketones), and the product yield was 98.73% based on 4-aminodiphenylamine.
[0048] Application Example 3 In a 100mL autoclave, 19.9g of 4,4-diaminodiphenylamine, 46.4g of acetone, and 3g of the catalyst of Example 2 were added, and then hydrogen was introduced to 3-4MPa, and the reaction temperature was controlled to be 120°C for ketoamine dehydration condensation. After the hydrogen pressure was lower than 2Mpa, hydrogen was introduced to 3-4Mpa until the hydrogen pressure no longer decreased. After the reaction was completed, it was detected that no by-product isopropanol was detected in the reaction mother liquor, and the remaining ketones and water were removed under reduced pressure to obtain the final antioxidant product 27.81g, the liquid phase purity (HPLC) was 99.5% (after deducting ketones), and the product yield was 98.27% based on 4,4-diaminodiphenylamine.
[0049] Application Example 4 In a 100mL autoclave, 10g of 4,4-diaminodiphenylamine, 50g of methyl isobutyl ketone, and 3g of the catalyst of Example 2 were added, and then hydrogen was introduced to 3-4MPa, and the reaction temperature was controlled to be 120°C for ketoamine dehydration condensation. After the hydrogen pressure was lower than 2Mpa, hydrogen was introduced to 3-4Mpa until the hydrogen pressure no longer decreased. After the reaction was completed, it was detected that no by-product methyl isobutyl methanol was detected in the reaction mother liquor, and the remaining ketone and water were removed under reduced pressure to obtain the final antioxidant product 18.18g, the liquid phase purity (HPLC) was 99.0% (after deducting ketone), and the product yield was 99.07% based on 4,4-diaminodiphenylamine.
[0050] Application Example 5 The antioxidant product was prepared according to the conditions of Application Example 1, except that the catalyst in Application Example 1 was repeatedly used. The results are shown in Table 1 below: Application Example 6 In a 100mL autoclave, 18.4g of 4-aminodiphenylamine, 50g of methyl isobutyl ketone, and 3g of different catalysts were added, and then hydrogen was introduced to 3-4MPa, and the reaction temperature was controlled to be 120°C, and ketoamine dehydration condensation was carried out. After the hydrogen pressure was lower than 2Mpa, hydrogen was introduced to 3-4Mpa until the hydrogen no longer decreased. After the reaction was completed, the alcohol content in the reaction mother liquor was detected, and then the alcohol, ketone and water were removed under reduced pressure to obtain the final antioxidant product. The catalyst used and the product situation are shown in Table 2 below.
[0051] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been presented as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to the equivalent embodiments of the same variations using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a catalyst for dehydration condensation reduction reaction, characterized in that The following steps are involved: (1) Spreading activated carbon in a fixed bed, and then continuously introducing a mixed solution of copper nitrate, zinc nitrate and zirconium nitrate into the fixed bed so that the mixed solution is in full contact with the activated carbon layer; (2) calcining the activated carbon after being fully contacted with the mixed solution to obtain activated carbon loaded with copper oxide-zinc oxide-zirconium oxide; (3) The activated carbon loaded with copper oxide-zinc oxide-zirconium oxide is dispersed in an organic solvent, and then a sulfiding agent is added to carry out a sulfidation reaction. After the reaction, the mixture is filtered, washed, and dried to obtain a catalyst for a dehydration condensation reduction reaction.
2. The preparation method according to claim 1, characterized in that: In step (1), at least one of the following conditions is included: a. The specific surface area of activated carbon is 1250-1350㎡ / g; b. The thickness of the activated carbon layer is 1.3-1.8cm; c. The flow rate of the mixed solution is 1-10 ml / min; d. In the mixed solution, the concentration of copper nitrate is 1-5 g / 100 ml, the concentration of zinc nitrate is 3-7 g / 100 ml, and the concentration of zirconium nitrate is 1-5 g / 100 ml; e. The temperature of the mixed solution when in contact with the activated carbon layer is 25-45°C, and the contact time is 0.5-2h.
3. The preparation method according to claim 1 or 2, characterized in that: In step (2), calcination is carried out in air at a temperature of 400-800° C. and a calcination time of 2-6 hours.
4. The preparation method according to claim 1, characterized in that: In step (3), the organic solvent is an alcohol, preferably methanol, ethanol or isopropanol.
5. The preparation method according to claim 1, characterized in that: In step (3), the vulcanizing agent is at least one of dimethyl sulfide, dodecanethiol, dimethyl sulfoxide, diphenyl sulfide, and diphenyl disulfide, and is preferably a mixture of diphenyl sulfide and diphenyl disulfide.
6. The preparation method according to claim 1 or 5, characterized in that: In step (3), the mass ratio of the activated carbon loaded with copper oxide-zinc oxide-zirconium oxide and the sulfiding agent is 5:0.1-1.
7. The preparation method according to claim 1, 4 or 5, characterized in that: In step (3), the vulcanizing agent is added in a dropwise manner for 2-5 minutes.
8. The preparation method according to claim 7, characterized in that: In step (3), the temperature for dropping the vulcanizing agent is 25-45°C, and the reaction is kept warm for 0.5-2h after the dropping is completed.
9. A catalyst prepared by the method for preparing a catalyst for dehydration condensation reduction reaction according to any one of claims 1 to 8.
10. Use of the catalyst according to claim 9 in a dehydration condensation reduction reaction of an aldehyde with an amine or a dehydration condensation reduction reaction of a ketone with an amine.
Citation Information
Patent Citations
Process for preparing 4,6-diamino resorcin hydrochlorate
CN101503364A
Catalyzed synthesis method of 3-amino-1, 2-propylene glycol
CN103319353A
Method for combined production of 3-methyl-1,5-pentanediol and C1-C6 alcohols
CN108191648A
Copper-based catalyst for synthesizing rubber anti-aging agent 6PPD and preparation and use methods
CN110152680A
Method for removing sulfur compounds from gases containing hydrocarbons
WO2004056949A1
Cited By
Preparation method for catalyst for dehydration-condensation reduction reaction, resulting product and use
WO2026113470A1